Non-Monetary Benefits of Continuous Training - Jens Ruhose; Stephan Thomsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study the effects of continuous training on non-monetary outcomes. Wider benefits of continuous training have become a top priority on the European political agenda. Using SOEP data, we find evidence that continuous training increases life satisfaction, reduces worries about the own economic and job situation, and increases civic participation in some domains. We employ a regression-adjusted DiD matching approach that accounts for selection on observables and for time-invariant unobservables.
Keywords: J24; I21; M53; 330